Implementasi Kebijakan Kepala Madrasah Dalam Meningkatkan Pelayanan Pendidikan Di MTs Negeri Kota Pasuruan - Herianto, Herianto (Inovasi: Jurnal Diklat Keagamaan, 2023)
This study aims to determine how the policy and its implementation as well as the supporting and inhibiting factors of the implementation of the madrasah prinsipal’s of policy in improving education services at State MTs of Pasuruan City. Researchers focused on the madrasah prinsipal’s of policy in improving education services. This research is qualitative research. Data collected using in-depth interviews, observation and documentation studies. After the data is collected, its validity is checked again through validation standards, namely trust, transferability, dependence, and firmness. The data analysis technique used is data reduction, presenting data and giving conclusions from the research results. The findings of this study are 1) The Education Service Policy carried out by madrasah to improve madrasah performance is quite good; 2) Implementation of the head master of Madrasah Policy through coordination and evaluation, the Madrasah Head can see the condition immediately all problems or plans that are running in the madrasah; 3) Supporting factors form madrasah is vice head master have a high spirit of cooperation, with dedication and loyalty in serving students according to their respective functions and responsibilities, Awareness of personnel in carrying out their respective duties, functions and obligations can be carried out properly, Adequate facilities and infrastructure. While the inhibiting factors are 1) Facilities and infrastructure are not sufficient to facilitate the needs of teachers and administrative employees; 2) reduced support from teachers and administrative personnel for the acceleration of the madrasah program; 3) There are some teachers who are still late and leave the hours empty when the learning process takes place; and 4) Some students who are not serious about taking extracurricular classes.